Analysis of the Effectiveness of the Hardening Temper Process to increase M8 Bolt Strength - Anrinal; Asmara Yanto; Dedi Kuswanto (Jurnal Teknik Mesin, 2021)
The purpose of this study was to analyze the effectiveness of the hardening-temper process on the strength of M8 bolts. The research was carried out through a hardening process with heating temperatures of 900°C, 1000°C, 1100°C, using a holding time of 15 minutes then quenched in aquadest cooling medium, then continued with a tempering process at the same tempering temperature of 400°C followed by cooling at room temperature. The torsional strength of the M8 bolt was obtained through torsional testing using the SM 1 MK II Torque Testing Machine. The results showed that the torsional strength of treated M8 bolts was lower than without treatment. Efforts to increase the torsional strength of M8 bolts with the hardening – tempering method are not recommended, because M8 bolts are made of low carbon steel which has low hardenability, so that the increase in torsional strength of M8 bolts is not significant.